Christian Communities and "Recovered Memories" of Abuse - Priest, Robert J. (Christian scholar's review, 2012)
In the 1980s the idea emerged that psychological problems are often caused by unremembered sexual abuse, and that healing requires retrieval of memory. While much of main-stream psychology later questioned the validity and/or reliability of such memories, many evangelical therapists and ministry leaders have continued to be “carriers” of recovered memory approaches. Using case study data, Robert Priest and Esther Cordill explore ways in which evangelical ministries and therapies foster “recovered memories,” and examine the implications for the accused. They call for Christian scholars to engage actively the ideas and practices underpinning populist evangelical therapies and ministries featuring recovered memory ideas.